Estrategias de comunicación para el posicionamiento de un modelo de imagen pública de liderazgo político en el contexto social actual en el cantón Machala, provincia de El Oro, año 2014. - Enríquez Chasin, Ruperto Ismael (2015)
This research is the public image of a political leader in election campaigns, which led to promote a study on the identification of major public marketing communication strategies, and, thus know the actions or activities that promote the construction and positioning, taking into account the social Canton Machala.